2016
DOI: 10.1186/s13071-016-1826-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation over a small spatial scale of the sand fly Lutzomyia vexator (Diptera: Psychodidae)

Abstract: BackgroundThe geographic scale and degree of genetic differentiation for arthropod vectors that transmit parasites play an important role in the distribution, prevalence and coevolution of pathogens of human and wildlife significance. We determined the genetic diversity and population structure of the sand fly Lutzomyia vexator over spatial scales from 0.56 to 3.79 km at a study region in northern California. The study was provoked by observations of differentiation at fine spatial scales of a lizard malaria p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…were both higher in this habitat for A. erythrurus . Thus, potential vectors of Lankesterella spp., such as sand flies (Diptera: Psychodidae; Telford, 2009 ), could find more heterogeneity of available microhabitats to thrive in the forest (Neal et al ., 2016 ; Megía-Palma et al ., 2017 ). Beside sand flies, other haematophagous dipterans feeding on lizards exist in the Mediterranean region, and thus, are potential vectors of haemococcidians.…”
Section: Discussionmentioning
confidence: 99%
“…were both higher in this habitat for A. erythrurus . Thus, potential vectors of Lankesterella spp., such as sand flies (Diptera: Psychodidae; Telford, 2009 ), could find more heterogeneity of available microhabitats to thrive in the forest (Neal et al ., 2016 ; Megía-Palma et al ., 2017 ). Beside sand flies, other haematophagous dipterans feeding on lizards exist in the Mediterranean region, and thus, are potential vectors of haemococcidians.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous studies on other sandfly species, many factors, including altitude, interpopulation distances, habitat modifications, anthropogenically induced-landscape fragmentation, vegetation types, geographic barriers, and interactions with host communities collectively contribute to the distribution, abundance, and genetic diversity of phlebotomine sandflies in Sri Lanka [13][14][15]. Those factors intertwine to shape the genetic landscape of these vectors, impacting their vectorial capacity and disease transmission dynamics.…”
Section: Introductionmentioning
confidence: 91%
“…This assumption simultaneously requires the dispersal of the vector to occur over short distances as not to disrupt the genetic structuring of P. mexicanum. Indeed, it has been found that the vector L. vexator disperses only minimally, staying mostly hidden in ground squirrel burrows and avoiding being carried over longer distances by wind currents [70].…”
Section: The Only Study Of Population Genetics Of Nematomorpha To Dat...mentioning
confidence: 99%
“…mexicanum and its reptile host [70]. Further, parasites may prove useful if the host is genetically uniform, as may often be the case with introduced/invasive species where we need to reconstruct their invasion history [106].…”
Section: Phylogeographic Triangulation and Trackingmentioning
confidence: 99%